Implementasi Pendidikan Literasi Keuangan pada Siswa Sekolah Dasar di Kecamatan Paseh, Kabupaten Bandung, Jawa Barat: Implementasi Pendidikan Literasi Keuangan pada Siswa Sekolah Dasar di Kecamatan Paseh, Kabupaten Bandung, Jawa Barat - Sheilla Putri Agustin; Aprianto La'lang Kuddy; Jenny Novianti Muliarahayu Soetedjo (Universitas Muhammadiyah Palembang, 2025)
Financial literacy is a fundamental life skill that should be introduced from an early age. However, its implementation among Indonesian children remains limited. This community service program aimed to improve elementary school students’ financial literacy through a contextual and interactive educational approach. The activity was conducted at SDN 2 Lokasari, Bandung, involving 48 students from grades IV to VI. The program included educational sessions and evaluations using pre and post-tests. The results revealed significant improvements in students' understanding of money management, distinguishing needs from wants, and recognizing financial institutions. This program has proven effective in fostering basic financial awareness and responsible financial behavior among school-aged children.